PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 017 BAGAN LIMAU KECAMATAN UKUI KABUPATEN PELALAWAN - ', Sambi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low results of students' mathematics learning class II SDNegeri 017 Bagan Limau Kecamatan Ukui. Of the 24 students only 14 students (61.7%),which reached the KKM. This study is a class action by applying quantum teaching learningmodel, the study was conducted in two cycles. The subjects were students of class II SDNegeri 017 Bagan Limau Kecamatan Ukui.. The collection of data used in the study was theobservation techniques and activities of students and teachers of mathematics achievementtest. This study obtained results that mathematics learning outcomes of students hasincreased, this is evidenced by: (a) the activities of teachers has increased, At the firstmeeting I cycle percentage is 53.66% increase to 64.29% in the first cycle of meetings 2. Incycle II meeting 1 increased to 73.81%. In the second cycle 2 meeting increased to 88.09%.Student activity also increased, in the first cycle of meeting 1 percentage was 54.76%increase to 61.91% in the first cycle 2. In cycle II meeting 1 meeting increased to 76.19%. Inthe second cycle 2 meeting increased to 85.72%; and (b) improving student learningoutcomes, the base score is the acquisition value of the average student was 70.7, an increasein the first cycle with the average value of 83.3 and the second cycle increased with anaverage value of 92.7 , Besides the number of students who completed the basic score is 14(61.7%), in the first cycle is the number of students who pass the 18 (76.4%) and the secondcycle is the number of students who pass the 21 (87.50%).